2019
DOI: 10.1021/acssuschemeng.9b03182
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effect of the Hydrophobic Block on the Chemical Stability of Ion-Conducting Multiblock Copolymers for Flow Battery

Abstract: Four sulfonated poly­(p-phenylene)-based ionomer materials with different hydrophobic block structures are synthesized in order to investigate the effect of the hydrophobic block structure on the durability of ionomer membrane in vanadium redox flow batteries (VRFBs). The structural differences of the hydrophobic blocks scarcely affect the physical, electrochemical, and morphological properties of the block copolymer-type ionomers. On the contrary, according to an ex situ soaking test and an in situ VRFBs cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Hong and Lee et al synthesized block copolymers of poly( p ‐phenylene) backbone and monomers with ether, biphenyl, carbonyl, and sulfonyl skeletons, and reported the VRFB properties and durability of those membranes 32 . The synthesized membranes show lower resistance and stable operation at higher current densities than Nafion 115.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong and Lee et al synthesized block copolymers of poly( p ‐phenylene) backbone and monomers with ether, biphenyl, carbonyl, and sulfonyl skeletons, and reported the VRFB properties and durability of those membranes 32 . The synthesized membranes show lower resistance and stable operation at higher current densities than Nafion 115.…”
Section: Resultsmentioning
confidence: 99%
“…The application of hydrocarbon (HC)‐type PEMs other than Nafion to VRFBs has recently been reported 19‐32 . Sun et al synthesized cationic and anion‐exchange membranes (AEM) with a phenylene backbone and found that the AEM had relatively high durability against V 5+ , and the performance of a VRFB constructed with AEM was comparable to that with Nafion 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the membrane morphological structure and properties are elaborated by the composition and operating conditions of a PPSU solution, including concentration, additives, solvent type, temperature, kinetic factors, the coagulation bath (phase inversion process), etc. [9][10][11][12][13][14][15][16]. Thermodynamics and kinetics play significant roles during membrane development [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A membrane having a high proton permselectivity against all vanadium ions is desired with good mechanical and chemical stabilities to keep the available charged capacity during the VRFB operation. 8 Various proton-conducting 9,10 or anion-conducting polymers 11,12 have been applied to VRFBs and are widely under investigation to replace the commercially available perfluorinated sulfonic acid membranes, which are expensive and have poor proton permselectivity against vanadium ions.…”
Section: ■ Introductionmentioning
confidence: 99%